Shareholder activism in Malaysia: is it effective? - Othman, Sarina; Borges, William G. (Elsevier, 2015)
Some recent developments associated with corporate governance and shareholder activism have shown that shareholder empowerment is vital nowadays. Hence, there is a dire need for minority shareholders to be more active and responsive in their dealings with corporations. Active shareholder engagement safeguards the interests and the rights of the minority shareholders from the effect of agency relationships and from the consequences of the unique atmosphere of shareholder activism in Malaysia. A conceptual discussion on shareholder activism has led to a conclusion that shareholder activism in developed countries cannot explain the state of activism in emerging economies, like Malaysia.